Endothelial Nitric Oxide Synthase (eNOS) 4a/b and G894T Polymorphisms and Susceptibility to Preeclampsia - Z Rahimi; A Aghaei; Z Rahimi; A Vaisi-Raygani (JRI, 2013)
Background: Preeclampsia is a pregnancy complication with unknown etiology and its incidence is associated with genetic and environmental factors. There are inconsistent reports related to the role of endothelial nitric oxide synthase (eNOS) 4a/b polymorphism on the risk of preeclampsia development. The aim of the present study was to investigate the possible influence of eNOS 4a/b and its synergism with eNOS G894T polymorphism on the risk of preeclampsia. Methods: The present case-control study consisted of 179 unrelated women with preeclampsia including 118 with mild and 61 with severe preeclampsia and 96 unrelated women with normal pregnancy as controls. All studied women were from Kermanshah Province of Iran. eNOS 4a/b and G894T genotypes were detected using polymerase chain reaction (PCR), and PCR-restriction fragment length polymorphism (RFLP) methods, respectively. The categorical variables between groups were compared using χ2 test and the Odds ratios (OR) were obtained by SPSS logistic regression. Statistical significance was assumed at p<0.05 level. Results: The frequency of eNOS a allele was slightly higher in both mild (16.5%) and severe (17.2%) preeclamptic women than controls (15.1%). Also, no significant difference was found between early- and late-onset preeclamptic women regarding the distribution of eNOS 4a/b genotypes. The presence of each allele of eNOS a or T was not associated with the risk of preeclampsia. However, the concomitant presence of both eNOS a and T alleles was associated with a non significant increased risk of severe preeclampsia by 1.77-fold (p=0.35). Conclusion: The present study indicates the lack of association between eNOS a and T alleles with the risk of mild preeclampsia and a non significant increased risk of severe preeclampsia in the presence of both alleles which needs to be investigated in a study with larger samples.
Keywords: eNOS 4a/b, eNOS G894T, Mild preeclampsia, Polymorphism, Severe preeclampsia